Effect of pre-exercise caffeine intake on endurance performance and core temperature regulation during exercise in the heat: a systematic review with meta-analysis - Naulleau, C.; Jeker, D.; Pancrate, T.; Claveau, P.; Deshayes, T. A.; Burke, L. M.; Goulet, E. D. B. (Sports Medicine, 2022)
Background: Heat is associated with physiological strain and endurance performance (EP) impairments. Studies have investigated the impact of caffeine intake upon EP and core temperature (CT) in the heat, but results are conflicting. There is a need to systematically determine the impact of pre-exercise caffeine intake in the heat. Objective: To use a meta-analytical approach to determine the effect of pre-exercise caffeine intake on EP and CT in the heat. Design: Systematic review with meta-analysis. Data Sources: Four databases and cross-referencing. Data Analysis: Weighted mean effect summaries using robust variance random-effects models for EP and CT, as well as robust variance meta-regressions to explore confounders. Study Selection: Placebo-controlled, randomized studies in adults (= 18 years old) with caffeine intake at least 30 min before endurance exercise = 30 min, performed in ambient conditions = 27 °C. Results: Respectively six and 12 studies examined caffeine`s impact on EP and CT, representing 52 and 205 endurance-trained individuals. On average, 6 mg/kg body mass of caffeine were taken 1 h before exercises of ~ 70 min conducted at 34 °C and 47% relative humidity. Caffeine supplementation non-significantly improved EP by 2.1 ± 0.8% (95% CI - 0.7 to 4.8) and significantly increased the rate of change in CT by 0.10 ± 0.03 °C/h (95% CI 0.02 to 0.19), compared with the ingestion of a placebo. Conclusion: Caffeine ingestion of 6 mg/kg body mass ~ 1 h before exercise in the heat may provide a worthwhile improvement in EP, is unlikely to be deleterious to EP, and trivially increases the rate of change in CT.